The Role of Mental Health Knowledge and Perceived Public Stigma in Predicting Attitudes towards Seeking Formal Psychological Help - Griselda Maria Ancela Wodong; Muhana Sofiati Utami (Faculty of Psychology, Universitas Gadjah Mada, 2023)
The low number of individuals seeking for professional help contributes to increased mental health problems. This study aims to examine attitudes toward seeking professional help regarding mental health knowledge, perceived public stigma, age, gender, and education. The participants involved were 701 people, aged between 19-49 years old. The research instruments were the ATSPPH-SF Scale, the MHLS Scale, and the PPMHS Scale. The multiple linear regression analysis results showed that mental health knowledge and perceived public stigma together played a role in the attitudes of seeking formal help (F=46,161; p0.05). The results of the independent t-test showed differences in attitudes toward seeking help based on gender and education level (p0.05). This study concluded that knowledge of mental health, gender, and education could predict the attitudes toward formal help-seeking, while perceived public stigma and age could not predict help-seeking attitudes.